Respiratory Burst Oxidase Homolog Gene A Is Crucial for Rhizobium Infection and Nodule Maturation and Function in Common Bean - Arthikala, Manoj-Kumar; Montiel, Jesús; Sánchez-López, Rosana; Nava, Noreide; Cárdenas, Luis; Quinto, Carmen (Frontiers in Plant Science, 2017)
Reactive oxygen species (ROS) produced by respiratory burst oxidase homologs (RBOHs) regulate numerous plant cell processes, including the symbiosis between legumes and nitrogen-fixing bacteria. Rapid and transient ROS production was reported after Phaseolus vulgaris root hairs were treated with Nod factors, indicating the presence of a ROS-associated molecular signature in the symbiosis signaling pathway. Rboh is a multigene family containing nine members (RbohA−I) in P. vulgaris. RNA interference of RbohB suppresses ROS production and attenuates rhizobial infection thread (IT) progression in P. vulgaris root hairs. However, the roles of other Rboh members in symbiotic interactions are largely unknown. In this study, we characterized the role of the NADPH oxidase-encoding gene RbohA (Phvulv091020621) in the P. vulgaris–Rhizobium tropici symbiosis. The spatiotemporal activity of the RbohA promoter colocalized with growing ITs and was associated with vascular bundles in developing nodules. Subcellular localization studies indicated that RBOHA was localized in the plasma membrane of P. vulgaris root hairs. After rhizobial inoculation, PvRBOHA was mainly distributed in the infection pocket and, to a lesser extent, throughout the IT. In PvRbohA RNAi lines, the rhizobial infection events were significantly reduced and, in successful infections, IT progression was arrested within the root hair, but did not impede cortical cell division. PvRbohA-RNAi nodules failed to fix nitrogen, since the infected cells in the few nodules formed were empty. RbohA-dependent ROS production and upregulation of several antioxidant enzymes was attenuated in rhizobia-inoculated PvRbohA-RNAi roots. These combined results indicate that PvRbohA is crucial for effective Rhizobium infection and its release into the nodule cells. This oxidase is partially or indirectly required to promote nodule organogenesis, altering the expression of auxin- and cyclin-related genes and genes involved in cell growth and division.